Immune response in Eimeria sp. and E. coli challenged broilers supplemented with amino acids - Gottardo, Elisangela T.; Burin Junior, Álvaro M.; Lemke, Bruna V.; Silva, Alexandra M.; Busatta Pasa, Cassiano L.; Muller Fernandes, Jovanir I. (Austral Journal of Veterinary Sciences, 2017)
The aim of this study was to evaluate the immune response of broiler chickens in Eimeria sp. and E. coli challenged broilers supplemented with glutamine, arginine and threonine. There were six hundred one-day-old male Cobb 500 broiler chickens. The design was completely randomised using a 2 x 3 factorial design (unchallenged and challenged x 3 diets). A commercial diet was used as a control and two other diets were formulated with glutamine (1.5 and 3% Aminogut®), arginine (1 and 2% L-Arginine), and threonine (1 and 2% L-threonine). At day 28, the birds fed the highest level of amino acid showed lower levels of IgA (P<0.05) compared to the control group, and resulted in an increased number of goblet cells. In the period of 1 week after the challenge, the challenged birds showed lower measures (P<0.05) of the thymus compared to the birds that had not undergone challenge. At day 28, unchallenged birds showed a reduction (P<0.05) in splenic measures in the treatment with the highest level of amino acids. The highest measures were correlated to control birds that were not challenged. At day 21, blood urea levels were increased (P<0.05) for birds fed amino acids supplementation compared to those which received no supplementation. After 28 days, uric acid levels were similar between the two supplemented diets. These results suggest that diet supplementation with amino acids above the recommended levels for growth may be necessary to improve the immune response against an Eimeria and E. coli challenge.